AB0575 Prevalence of hla-cw * 06 and * 07 and its relationship with psoriatic arthritis in northwestern spain. (23rd January 2014) - Blanco, E. A.; Bejerano, C.; Pinto-Tasende, J.; Pértega, S.; Rego, I.; Fernandez, C.; Freire, M.; De Toro, J.; Blanco, F. J.; Fernández-Sueiro, J. L.
Abstract : Background: Psoriatic arthritis (PsA) is a disease developed in 10-20% of psoriasis patients. HLA–Cw*06 has been identified as the major genetic determinant of susceptibility to psoriasis. Objectives: To estimate the prevalence of HLA-Cw6 and Cw7 in healthy population, patients with psoriasis without joint disease and patients with PsA and to analyze the influence of both alleles in the characteristics of PsA. Methods: Genotyping of HLA-Cw * 06 and * 07 was performed on DNA samples of 390 Caucasian subjects by PCR-SSP (Sequence specific primer). The allele frequencies of HLA-Cw * 06 and * 07 were determined in patients with psoriasis (n = 117), PsA (n = 172), and compared with those of healthy controls (n = 101), and we calculated the odds ratio and confidence interval of 95% (OR, 95% CI). We determined the association of alleles with clinical-radiological forms of PsA (peripheral and axial / mixed). We used the chi-square test, Fisher's exact test and t Student. We consider to be significant at p <0.05. Results: The frequencies of HLA-Cw * 06 were higher in type 1 psoriasis (OR 7.1, 95% CI 1.8-27.9, P <0.0001) and PsA (OR 3.5, 95% CI 1.7-7.3, P 0.001) relative to healthy controls, thus, in HLA-Cw * 06 positive patients with psoriasis, the diagnosis was at younger ages, 19.4 years (SD 12.5) vs 34.8 (18.8), p <0.0001) but not in PsA (p 0.941); although PsA patients with type I psoriasis had been diagnosed before patients with type II psoriasis (40.0 years (12.2) vs 57.6 (9.7), p <0.0001) regardless of the alleles. HLA-Cw * 0602 was associated with type I psoriasis (OR 3.3, 95% CI 1.5-7.1, p 0003) and PsA (OR 3.5, 95% CI 1.7-7.3, p 0.001) compared to healthy controls, but there were no differences in the HLA-Cw * 0602 prevalence between clinical-radiological forms of APs neither in clinical and laboratory features, metrology and radiological damage. PsA patients with type I psoriasis had a higher prevalence of HLA-Cw * 0602 than PsA patients with type II psoriasis (p 0.001). No differences were observed for the HLA-Cw * 07 and its subtypes relative to healthy controls or patients with psoriasis. Conclusions: HLA-Cw * 06 and its main subtype * 0602, are more prevalent in our patients with cutaneous psoriasis and psoriatic arthritis compared with healthy controls, and are more frequent in patients with a diagnosis of an earlier age. There was no influence on other features analyzed in PsA patients We found no difference in HLA-Cw * 07. Acknowledgements: The authors thank José Luis Fernández-Sueiro for him hard work and dedication. Rest in peace. Disclosure of Interest: None Declared